Violencia sexual y su afectación emocional en un paciente de 15 años del cantón Puebloviejo - Espinoza Ponce, Angy Gabriela (2023)
The objective of this case study is to determine the emotional impact caused by a rape in a 15-year-old adolescent from the Puebloviejo canton, in order to expose the relevant aspects of how the mental health of the adolescent is altered. . Evidencing signs and symptoms that are evolving in the adolescent and this generates a depressive picture on it according to the results that were obtained with the respective report of the clinical history, where all the relevant information is presented. In this case study, techniques such as the interview, the adolescent's clinical history, and psychometric tests were used, including the Beck depression inventory, the hopelessness scale test, and the social skills evolution test. where it was possible to verify a level of severe depression, therefore the high hopelessness level in terms of social skills presents a low level, obtaining as results in the assessment of the adolescent with a severe depressive disorder without psychotic symptoms, therefore a favorable prognosis for reasons that the patient of her own free will made the decision to improve.